The use of gut microbiota probiotics in the management of atopic dermatitis in children: systematic review - Wedayanti, Desak Putu Kunti (International Journal of Research in Medical Sciences, 2023)
Atopic dermatitis (AD) is one of the most common inflammatory skin diseases, affecting more than 20% of the population at some time in their lives. Currently, corticosteroids are generally used for the treatment of AD, although these drugs have the potential to cause more serious side effects. Objective of the study was to find out the role of probiotics in the management of atopic dermatitis in children through a review of previous research. A PubMed search was carried out with the keywords ’atopic dermatitis’ and ’probiotic’ from databases for the last 10 years (2014-2023). Researchers present the results in narrative form and in table form. A total of 10 articles were included in this study. The research comes from several different countries with the research time being from 2017 to 2022. Each study describes the author, year of study, total sample, type of probiotic, duration of treatment, results and side effects. Giving probiotics to pediatric patients with atopic dermatitis has an impact on reducing SCORAD in evaluation after 2-3 months (8-12 weeks). No significant side effects were found in the included studies.